Penerapan Jurnalisme Pembangunan dalam Pemberdayaan Masyarakat (Adopsi Inovasi Urban Farming dan Pemanfaatan Lahan Tidur di Kota Palembang) - Sumaina Duku (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2018)
Development journalism and community empowerment have become interesting things lately especially the existence of an urban farming program which is believed to be able to empower the urban poor. The media supports the urban farming program as a community empowerment program. This study aims to look at the application of development journalism in community empowerment. The results of the study show that development journalism has been implemented in the city of Palembang with the coverage of local government programs by various media in South Sumatra, one of which is the Urban Farming program, which is a regional government program in Palembang in collaboration with Bank Indonesia. Furthermore, the role of development journalism in community empowerment in the city of Palembang can be seen with enthusiasm by the community in utilizing vacant land to carry out urban farming which is a regional government program in collaboration with Bank Indonesia to be a program that can help the community economy where the mass media in Palembang are active preach this program so that people are interested in participating in this program both directly and indirectly. The pattern of adoption of urban farming innovations and utilization of idle land in the city of Palembang is divided into innovators, early adopters, and early majorities.